1984
DOI: 10.1115/1.3243096
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Uncertainty Analysis of Hot-Wire Data

Abstract: Uncertainty analysis of hot-wire data in turbulent flows are made for time-averaging and real-time data reduction techniques. Equations of uncertainty are derived in general form for every step of data taking and evaluation. Numerical examples are supplied for two-dimensional flat plate boundary layer data. Results show that the real-time data reduction techniques generally have a lower and much more uniform uncertainty distribution than the time-averaging techniques (whose uncertainties are much higher for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…Dantec single and X-array probes, types 55Pll, 14, 61 and 64, operated using Prosser type 6110 anemometer bridges interfaced to the PET computer, were used. Where necessary hot-wire mea- surements were corrected for the effects of high local turbulence levels using the methods of Tutu and Chevray (1975) and Yavuzkurt (1984). All probes were introduced to the flow through ports in the wall of the pipe.…”
Section: Apparatus and Instrumentationmentioning
confidence: 99%
“…Dantec single and X-array probes, types 55Pll, 14, 61 and 64, operated using Prosser type 6110 anemometer bridges interfaced to the PET computer, were used. Where necessary hot-wire mea- surements were corrected for the effects of high local turbulence levels using the methods of Tutu and Chevray (1975) and Yavuzkurt (1984). All probes were introduced to the flow through ports in the wall of the pipe.…”
Section: Apparatus and Instrumentationmentioning
confidence: 99%
“…Yavuzhurt (1984) calculated the errors in the Uem and ui by estimating the 0(2) terms in equations (A.6) using the data from Klebanoff and found that the total errors were less than 1-1.5% (assuming K,=0.2 and K 2 -1.02). …”
Section: Iw 2 W;mentioning
confidence: 99%
“…[28] is used to quantify the experimental uncertainties. The independent parameters such as atmospheric pressure, curve fitting error in calibration, A/D resolution uncertainty, probe positioning and humidity are considered in the uncertainty analysis.…”
Section: Methodsmentioning
confidence: 99%